Monel single crystal copper wire material and method of making same
By combining vertical roll-to-roll technology with copper wire single crystallization and graphene CVD, the problems of deformation and polycrystalline formation in the continuous growth of copper wire were solved, resulting in high-quality graphene-coated single-crystal copper wire, which improves conductivity and enables continuous production.
Patent Information
- Application Number
- CN202511604157.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-01-23
- Estimated Expiration
- 2045-11-05
AI Technical Summary
Existing technologies struggle to produce high-quality single-crystal copper wire and graphene composite materials at low cost and high efficiency. In particular, during the continuous growth of copper wire, issues such as copper wire deformation, polycrystalline formation, and weak graphene bonding exist, affecting electrical and thermal conductivity.
By employing a vertical roll-to-roll technique combined with copper wire single crystallization and graphene chemical vapor deposition, and through a specific temperature gradient and non-contact annealing, copper wire single crystallization and graphene coating are achieved, controlling the copper wire to remain undeformed at high temperatures and ensuring the quality of graphene crystallization.
The single crystallization and graphene coating of copper wire were achieved, which significantly improved the conductivity of copper wire, reaching 112.8% IACS, exceeding the performance of silver, and enabled continuous production.
Smart Images

Figure CN121046824B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials, specifically relating to a montmorillonite single-crystal copper wire material and its preparation method. Background Technology
[0002] Copper wire is a commonly used material in electronic equipment and power systems. High-performance copper wire materials often need to possess excellent electrical conductivity and mechanical strength, while also meeting application requirements such as long-term stable operation under certain high-temperature environments. Single-crystal copper wire has superior electrical conductivity, thermal conductivity, and signal transmission properties compared to ordinary polycrystalline copper wire. With the rapid development of semiconductor and integrated circuit technologies, single-crystal copper wire is gradually replacing gold wire and is widely used in important scenarios such as ultra-fine bonding wires for integrated circuits, high-fidelity signal transmission, and high-standard communication network cable transmission.
[0003] Graphene is a material composed of carbon atoms... sp2 Hybridized single-layer or few-layer two-dimensional crystalline materials possess excellent electrical, thermal, and mechanical properties. Combining graphene with copper wire to create graphene-copper wire holds promise for breakthroughs in the electrical conductivity, thermal conductivity, current carrying capacity, and service stability of copper wire, making it an ideal candidate for next-generation high-conductivity wires (cables) with the potential to have a significant impact on industries such as electronics, power, energy, thermal management, and aerospace.
[0004] For single-crystal copper wire, there are currently two main preparation routes for commercially available products. One route involves first preparing single-crystal copper ingots or rods, then drawing them into wires and performing an additional single-wire annealing process. During the processing of copper wire / wire materials, as the deformation increases, the copper material undergoes severe deformation, leading to further increases in defects such as grain breakage, vacancies, dislocations, and cracks within the grains and at grain boundaries. This increases internal stress, hindering the directional migration of electrons. Simultaneously, lattice distortion at defects and interfaces increases the probability of electron and phonon scattering, reducing the electrical and thermal conductivity of the copper material and increasing signal transmission losses. The additional single-wire annealing process not only increases the complexity and cost of the process but also requires further addressing the polycrystalline transformation caused by copper recrystallization (driven by processing stress) during annealing. The other preparation route involves directly pulling single crystals from molten copper and forming copper wires of a certain diameter through continuous casting, also known as thermoforming continuous casting technology. The problem with continuous casting for preparing single-crystal copper wire is that the equipment needs to maintain a temperature of 1190℃~1350℃ or higher for a long time to maintain the high temperature of the copper molten pool, resulting in very high equipment costs and energy consumption.
[0005] Currently, graphene copper wire is produced using graphene copper powder as raw material through processes such as hot pressing composite, forging, and drawing. In this process, graphene may suffer from low crystallinity, weak interfacial bonding, and small size of continuous graphene. The rods obtained from powder composites may have insufficient density, poor interpowder bonding, and decreased mechanical properties. Furthermore, copper wires drawn with large deformation generally exhibit more processing defects and smaller grain sizes, negatively impacting electrical and thermal conductivity.
[0006] Chemical vapor deposition (CVD) on copper substrates has been widely recognized in recent years as the most mature method for preparing high-quality graphene and the most competitive method for preparing graphene-copper composites. CVD growth of high-quality graphene requires either sufficient pyrolysis of the carbon source species, deposition at temperatures close to the melting point of copper (>1000℃), or additional energy at lower growth temperatures, such as using plasma-enhanced chemical vapor deposition (PECVD) to promote carbon source pyrolysis.
[0007] The mechanical properties of copper decrease significantly at high temperatures. To ensure the quality of graphene crystallization while avoiding copper wire deformation, two approaches are necessary: 1) Static chemical vapor deposition (CVD) can be used to reduce the tension introduced by the dynamic movement of the material during growth, but this approach suffers from insufficient preparation efficiency and the inability to achieve continuous production of long copper wires; or 2) Plasma-enhanced chemical vapor deposition (PECVD) can be used to lower the growth temperature as much as possible. However, the 700℃~900℃ temperature typically used for PECVD is far higher than the recrystallization temperature of copper (300℃~400℃) and lower than the typical temperature for abnormal grain growth in copper (~980℃). This results in a significant decrease in the tensile strength of copper, affecting the reliability of unwinding and winding during continuous roll-to-roll growth, and the grain size also fails to grow effectively, weakening the improvement of the conductivity of the copper material itself. Furthermore, at this temperature, the PECVD method also faces challenges in controlling the quality of graphene crystallization and the nucleation density. Therefore, there is an urgent need to develop a graphene-copper wire preparation technology that simultaneously achieves high-quality graphene and high continuous growth efficiency.
[0008] Existing roll-to-roll technology systems, besides enabling graphene CVD growth, can also achieve copper foil monocrystallization to some extent. However, compared to copper foil, the high-temperature heat treatment and annealing monocrystallization process of copper wire faces three additional significant challenges: 1) The tensile strength of pure copper at 1000℃ is generally less than 20 MPa, while the cross-sectional area of copper wire is much smaller than that of copper foil. This means that under the same conditions, the breaking force of copper wire is 2-4 orders of magnitude lower than that of copper foil; 2) Unlike the columnar grains in the original rolled copper foil, the original grains in drawn copper wire are generally elongated and have a specific texture. The driving force for further axial growth of abnormal grains at high temperatures is limited; 3) Copper wire has two dimensions on the micrometer scale, and the impact of copper volatilization at high temperatures on the wire diameter must be considered. For example, in a hydrogen atmosphere below 200 Pa, the volatilization rate of copper reaches 4.30 × 10⁻⁶. - 7 At this rate (kg / (m²·s), a 50 μm diameter copper wire will lose more than 1.5% of its cross-sectional area for every hour of annealing at 1000℃. Therefore, ordinary roll-to-roll CVD systems cannot meet the requirements for continuous CVD growth and single crystallization of copper wires. Summary of the Invention
[0009] To overcome the aforementioned shortcomings, this invention combines vertical roll-to-roll technology, single-crystalization of copper wire, and chemical vapor deposition growth of graphene to provide a continuous preparation method for graphene-coated single-crystal copper wire materials. This method is suitable for single-crystalization of copper wires of different diameters and high-quality graphene coating. This invention combines copper wire single-crystalization, high-temperature graphene growth, and roll-to-roll continuous preparation. At temperatures below the melting point of copper (<1083℃, far lower than the 1190℃~1350℃ of continuous casting), through a specific temperature gradient and non-contact annealing, continuous growth of abnormal grains is achieved. Furthermore, high-quality graphene growth and coating are completed simultaneously with copper wire single-crystalization, resulting in graphene-copper wire materials (graphene-copper wire) with ultra-long copper single-crystal dimensions. Tests showed that, in terms of electrical conductivity, the monocrystalline copper wire (112.8% IACS) exhibited the best performance compared to the polycrystalline copper wire (106.5% IACS), monocrystalline copper wire (105.1% IACS), and original copper wire (94.2% IACS).
[0010] The continuous preparation method of montmorillonite single-crystal copper wire material provided by the present invention includes the following steps:
[0011] Using vertical roll-to-roll technology, copper wire is secured to the unwinding shaft in the lower unwinding chamber, with its starting end passing through the tubular furnace body from bottom to top and fixed to the winding shaft in the upper winding chamber. Simultaneously, the suspended section of the copper wire remains free from contact with other objects. A specific tension is applied at the winding end, and a specific temperature gradient is applied along the direction of copper wire movement at a certain winding speed to promote continuous growth of copper single-crystal grains. Meanwhile, carbon source gas is introduced into the chamber, and graphene is grown via chemical vapor deposition. After continuous growth, graphene-coated single-crystal copper wire material, i.e., graphene single-crystal copper wire material, is obtained.
[0012] In the above method, the diameter of the copper wire can be 50 μm to 2 mm, specifically 50 μm to 200 μm;
[0013] The copper wire is a commercially available copper wire raw material;
[0014] The above method is implemented using a vertical roll-to-roll CVD equipment, wherein the winding and unwinding mechanism of the vertical roll-to-roll CVD equipment is equipped with a precision tension control unit.
[0015] During roll-to-roll CVD growth, the copper wire is simultaneously subjected to the tension of winding and the stretching effect of its own weight. To ensure that the copper wire is neatly bundled during continuous operation, an additional tension greater than the weight of the copper wire should be applied at the winding end. However, in order to prevent the copper wire from undergoing plastic deformation during the high-temperature CVD process, it is necessary to precisely control the winding tension to be less than a certain specific value.
[0016] This invention experimentally determined the relationship between the maximum winding tension and the copper wire diameter and heat treatment temperature. Optionally, when the CVD growth temperature is ≥940℃ and the copper wire diameter is 200~400 μm, the tension applied at the winding end is... F Satisfying 8 mN≤ F ≤0.3N; when the copper wire diameter is 50~100μm, the tension F applied at the winding end satisfies 0.5 mN≤ F ≤0.02 N.
[0017] The winding speed R (i.e., the continuous preparation rate of montmorillonite single-crystal copper wire) satisfies 10 mm / min ≤ R ≤100mm / min.
[0018] When the winding speed is too fast (e.g., greater than 100 mm / min), the copper wire stays in the high-temperature zone for a short time, and the copper grains cannot grow completely to form a whole single crystal, so only polycrystalline copper wire with montmorillonite can be obtained; while if the winding speed is too slow, the preparation efficiency is too low.
[0019] Along the direction of copper wire movement, the temperature gradient increases, and the temperature gradient is 0.5~4℃ / cm, with a maximum temperature of 980~1040℃, specifically 1020℃;
[0020] Optionally, the temperature gradient is achieved by setting different temperatures in each heating zone of the CVD furnace.
[0021] In one embodiment of the present invention, the CVD furnace body is provided with 5 temperature zones, each zone being 10cm in length, and the temperatures of each zone along the running direction of the copper wire are: 980℃, 990℃, 1000℃, 1010℃, and 1020℃.
[0022] In the above method, the total pressure of the chamber is not less than 2000 Pa, and can be selected as 90 kPa to atmospheric pressure (101 kPa) to suppress the high-temperature volatilization of copper to the greatest extent.
[0023] The carbon source gas is methane or acetylene.
[0024] Specifically, the preparation of monolayer graphene-coated montmorillonite single-crystal copper wires was controlled at 1 Pa ≤ P CH4 ≤5 Pa, or 0.05 Pa≤ P C2H2 ≤0.2 Pa, 100 Pa≤ P H2 ≤1000 Pa, P CH4 、P C2H2 、P H2 These are the partial pressures of methane, acetylene, and hydrogen, respectively, with high-purity argon serving as a supplementary atmosphere to balance the pressure.
[0025] Preparation of bilayer and few-layer graphene-coated montmorillonite single-crystal copper wires with Pa controlled at 10 ≤ P CH4 ≤50 Pa, or 0.2 Pa≤ P C2H2 ≤1 Pa, 2000 Pa≤ P H2 ≤20000 Pa, P CH4 、P C2H2 、P H2 These are the partial pressures of methane, acetylene, and hydrogen, respectively, with high-purity argon serving as a supplementary atmosphere to balance the pressure.
[0026] The graphene-coated single-crystal copper wire material, after roll-to-roll growth, forms a neatly coiled shape.
[0027] Optionally, multiple independently wound copper wires with a certain interval can be placed at the unwinding end to achieve coaxial parallel growth of multiple wires.
[0028] The graphene-coated single-crystal copper wire material prepared by the above method also falls within the scope of protection of this invention.
[0029] This invention also provides a continuous preparation method for single-crystal copper wire material. The method includes the following steps: using vertical roll-to-roll technology, the copper wire is fastened to the unwinding shaft in the lower unwinding chamber, so that its starting end passes through the tubular furnace body from bottom to top and is fixed to the winding shaft in the upper winding chamber; a specific range of tension is applied at the winding end; and a specific temperature gradient is applied along the copper wire running direction at a certain winding speed to promote the continuous growth of copper wire grains.
[0030] Normally, copper wires deform or even break under very small tensile stress at high temperatures, and cannot be effectively wound into bundles without any tensile stress. In the continuous fabrication of copper wires in traditional horizontal roll-to-roll systems, a large tension is often required to ensure the horizontal movement of the copper wire and overcome its resistance to the substrate. During this process, the copper wire is highly susceptible to deformation or even breakage; simultaneously, friction on the side of the copper wire in contact with the substrate can cause graphene damage. This invention solves the problem of difficult-to-control tensile stress in copper wires at near-melting-point temperatures through a vertical roll-to-roll system and tension control mechanism, achieving stable, rapid, and continuous execution of copper wire annealing and single-crystalization with surface graphene growth.
[0031] Furthermore, this invention addresses the textural characteristics of slender grains in copper wires by improving contactless annealing and temperature gradient annealing methods based on copper foil, thus enabling the preparation of ultra-long single-crystal copper wires. Further, by combining this with the CVD growth process of graphene, the high-temperature volatilization of copper is significantly suppressed, achieving continuous preparation of graphene single-crystal copper wires with different numbers of graphene layers. Simultaneously, the surface graphene film exhibits extremely high crystallinity.
[0032] Comparative analysis showed that both copper wire monocrystallization and surface graphene coating improved the conductivity (94.2% IACS) of the original copper wire by 10-12%. This invention achieves an effective combination of the two processes mentioned above, obtaining the graphene monocrystallized copper wire through a one-step high-temperature treatment, achieving a conductivity of 112.8% IACS, exceeding the 108% IACS of silver. Attached Figure Description
[0033] Figure 1 The images show (a) a physical diagram, (b) a schematic diagram, and (c) the temperature settings for each temperature zone of the vertical roll-to-roll chemical vapor deposition growth apparatus used in this invention.
[0034] Figure 2 Scanning electron microscopy images and electron backscatter diffraction characterization of the original copper wire material.
[0035] Figure 3Scanning electron microscopy images and electron backscatter diffraction characterization of the montmorillonite single-crystal copper wire prepared in Example 1 of this invention.
[0036] Figure 4 This is a scanning electron microscope image of the microstructure of graphene on the surface of the montmorillonite single-crystal copper wire prepared in Example 1 of the present invention.
[0037] Figure 5 The typical Raman spectrum of the montmorillonite single-crystal copper wire prepared in Example 1 of this invention.
[0038] Figure 6 A photograph of the 50-meter-long montmorillonite copper wire prepared.
[0039] Figure 7 Scanning electron microscopy images and electron backscatter diffraction characterization of the polycrystalline copper wire prepared for Comparative Example 1.
[0040] Figure 8 The following are the EDS elemental analysis results for the original commercial copper wire, the annealed single-crystal copper wire, and the graphene-coated single-crystal copper wire prepared in Example 1.
[0041] Figure 9 The conductivity measurements are for the original commercial copper wire, annealed monocrystalline copper wire, graphene-coated monocrystalline copper wire prepared in Example 1, and montmorillonite polycrystalline copper wire prepared in Comparative Example 1.
[0042] Figure 10 The stress distribution measurement results are for the graphene-coated single-crystal copper wire prepared in Example 1.
[0043] Figure 11 The image shows a scanning electron microscope image of the multilayer graphene-copper wire prepared in Example 2 of this invention.
[0044] Figure 12 The relationship between critical breaking force and growth temperature is shown for two typical copper wire diameters during roll-to-roll growth.
[0045] Figure 13 This is a schematic diagram of three bundles of copper wires growing coaxially and in parallel in the same furnace.
[0046] Figure 14 This is a schematic diagram illustrating the principle of horizontal roll-to-roll growth.
[0047] Figure 15 This is a photograph of a copper wire after horizontal roll-to-roll growth and winding.
[0048] Figure 16 This is a scanning electron microscope image of the contact side between the copper wire and the carrier after horizontal roll-to-roll growth. Detailed Implementation
[0049] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0050] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0051] Example 1: Roll-to-roll single crystallization and surface graphene growth of 20 m long, 200 μm diameter copper wire
[0052] 1) Secure the neatly bundled commercial copper wire material to the... Figure 1 The copper wire is placed on the unwinding shaft of the lower unwinding chamber of the vertical roll-to-roll chemical vapor deposition (CVD) growth apparatus shown. The beginning end of the copper wire is then passed through the tubular furnace body and fixed to the winding shaft of the upper winding chamber. The winding tension is set to 0.3 N, and the copper wire is suspended in the air and does not contact other objects. The CVD high-temperature reaction chamber is then evacuated to low pressure.
[0053] 2) Under an inert atmosphere (argon, partial pressure 90 kPa), the CVD reaction chamber is heated from room temperature to the target temperature within 1 h. The temperatures of the five temperature zones from bottom to top are set to 980℃, 990℃, 1000℃, 1010℃ and 1020℃ respectively, and the length of each temperature zone is about 10 cm.
[0054] 3) Maintain the chamber temperature and switch the gas to a mixture of argon, hydrogen and acetylene (argon is used as a supplementary gas to balance the pressure), argon 90 kPa, hydrogen 1 kPa, acetylene 0.1 Pa.
[0055] 4) Start the unwinding and rewinding mechanisms, and set both the unwinding and rewinding speeds to 100 mm / min.
[0056] 5) Maintain the conditions described in 3) until the copper wire bundle completes continuous single crystallization and graphene growth and is completely wound to the take-up end.
[0057] Figure 1 The diagram shows the physical image (a) and schematic diagram (b) of the vertical roll-to-roll CVD growth system used, as well as the temperature settings for each temperature zone (c). Tension control systems are included at both ends of the winding and unwinding.
[0058] Figure 2 SEM images and EBSD characterization results of the commercial copper wire raw materials used.
[0059] Figure 3The SEM images and EBSD characterization results of the prepared montmorillonite single-crystal copper wire are shown. The EBSD scan images show that the IPF-Z colors of the sample are consistent, proving that the obtained copper wire is a single crystal.
[0060] Figure 4 The image shows the microscopic SEM morphology of graphene on the surface of the copper wire after CVD growth. It can be seen that under this process, the single layer of graphene completely covers the surface of the copper wire.
[0061] Figure 5 The typical Raman spectrum of the graphene copper wire obtained by this process shows that no obvious defect D peak was observed, indicating that the graphene crystallization quality is excellent.
[0062] The 50 m-length montmorillonite copper wire (e.g., montmorillonite copper wire) was continuously prepared using the process described in Example 1 of this invention. Figure 6 (As shown).
[0063] Comparative Example 1: Roll-to-roll growth of graphene on the surface of a 200 μm diameter copper wire at a winding speed of 1000 mm / min.
[0064] 1) Secure the neatly bundled commercial copper wire to the unwinding shaft in the lower unwinding chamber. Then, pass the beginning of a 200 μm diameter copper wire through the tubular furnace body and fix it to the winding shaft in the upper winding chamber. Set the winding tension to 0.3 N, ensuring the copper wire is suspended and not in contact with other objects. Reduce the CVD high-temperature reaction chamber to low pressure.
[0065] 2) Under an inert atmosphere (argon, partial pressure 90 kPa), the CVD reaction chamber is heated from room temperature to the target temperature within 1 hour. The temperatures of the five temperature zones from top to bottom are set to 980℃, 990℃, 1000℃, 1010℃ and 1020℃ respectively, and the length of each temperature zone is about 10 cm.
[0066] 3) Maintain the chamber temperature and switch the gas to a mixture of argon, hydrogen and acetylene (argon is used as a supplementary gas to balance the pressure), argon 90 kPa, hydrogen 1 kPa, acetylene 0.1 Pa.
[0067] 4) Start the unwinding and rewinding mechanisms, and set both the unwinding and rewinding speeds to 1000 mm / min.
[0068] 5) Maintain the conditions described in 3) until the copper wire bundle is completely wound to the take-up end.
[0069] Figure 7The SEM images and EBSD characterization results of the obtained graphene copper wire show that complete graphene film coverage can be achieved under the rapid preparation conditions of 1000 mm / min. However, due to the short residence time of the copper wire in the high-temperature region, the copper grains failed to grow completely to form a single crystal. The product obtained is a polycrystalline graphene copper wire, and its conductivity is measured to be 106.5% IACS, which is lower than the 112.8% IACS of the single-crystal graphene copper wire.
[0070] The EDS elemental analysis results of the original commercial copper wire, the annealed single-crystal copper wire (in Example 1, no carbon source gas was introduced, and other process conditions were the same), and the montmorillonite single-crystal copper wire prepared in Example 1 are as follows: Figure 8 As shown. By Figure 8 It can be seen that compared with the original copper wire, the contents of oxygen, nitrogen, and sulfur impurities in annealed single-crystal copper wire and montmorillonite single-crystal copper wire are significantly reduced, especially the montmorillonite single-crystal copper wire, which has the lowest oxygen content. The carbon content, mainly due to adsorption of carbon from the atmosphere, did not show significant differences among the different samples.
[0071] Figure 9 The conductivity measurements are for the original copper wire, the annealed single-crystal copper wire, the montmorillonite single-crystal copper wire prepared in Example 1, and the montmorillonite polycrystalline copper wire prepared in Comparative Example 1. Figure 9 It can be seen that single-crystallization of copper wire (105.1% IACS) and surface graphene coating (106.5% IACS) both improve the conductivity of the original copper wire (94.2% IACS). The single-crystallized copper wire with graphene prepared by Example 1 has a conductivity of 112.8% after synergistic enhancement, which even exceeds that of silver (108% IACS).
[0072] Figure 10 The stress distribution measurement results are shown for the graphene-coated single-crystal copper wire prepared in Example 1. A series of XRD characterizations confirmed the existence of compressive stress within the graphene-coated single-crystal copper wire, which theoretically contributes positively to further improving the conductivity of the copper wire.
[0073] Example 2: Roll-to-roll growth of multilayer graphene on the surface of a 200 μm diameter copper wire
[0074] 1) Secure the neatly bundled commercial copper wire to the unwinding shaft in the lower unwinding chamber. Then, pass the beginning of a 200 μm diameter copper wire through the tubular furnace body and fix it to the winding shaft in the upper winding chamber. Set the winding tension to 0.3 N, ensuring the copper wire is suspended and not in contact with other objects. Reduce the CVD high-temperature reaction chamber to low pressure.
[0075] 2) Under an inert atmosphere (argon, partial pressure 90 kPa), the CVD reaction chamber is heated from room temperature to the target temperature within 1 hour. The temperatures of the five temperature zones from top to bottom are set to 980℃, 990℃, 1000℃, 1010℃ and 1020℃ respectively, and the length of each temperature zone is about 10 cm.
[0076] 3) Maintain the chamber temperature and switch the gas to a mixture of argon, hydrogen and acetylene (argon is used as a supplementary gas to balance the pressure), argon 90 kPa, hydrogen 2 kPa, acetylene 1 Pa.
[0077] 4) Start the unwinding and rewinding mechanisms, and set both the unwinding and rewinding speeds to 100 mm / min.
[0078] 5) Maintain the conditions described in 3) until the copper wire bundle completes continuous single crystallization and graphene growth and is completely wound to the take-up end.
[0079] Figure 11 Scanning electron microscopy image of the multilayer graphene-single crystal copper wire prepared in this embodiment.
[0080] Comparative Example 2: Fracture of a 200 μm diameter copper wire during continuous roll-to-roll growth.
[0081] The rest is the same as in Example 1, except that the winding tension in step 1) is set to 1 N, that is, during the subsequent high-temperature growth process of the entire roll-to-roll, a tensile stress of about 1 N is applied to the copper wire between the winding and unwinding sections.
[0082] In this comparative example, during the growth process at 1020℃ in the CVD system, the tensile stress of 1 N exceeded the breaking strength of the 200 μm diameter copper wire, causing the copper wire to break rapidly and making continuous roll-to-roll preparation impossible.
[0083] In this process, the actual tension that the copper wire can withstand is related to the yield / fracture strength of the material itself, the cross-sectional area of the copper wire, and the CVD temperature. Figure 12 This paper focuses on illustrating the relationship between critical breaking force and growth temperature during the roll-to-roll growth process of copper wires with two typical wire diameters (200 μm and 500 μm).
[0084] Example 3: Three bundles of copper wires grow coaxially and in parallel in the same furnace
[0085] The rest is the same as in Example 1. In step 1), the three bundles of neatly bundled commercial copper wire raw materials are fastened to the unwinding shaft in the lower unwinding chamber, and the starting ends of the three bundles of copper wire are independently passed through the tubular furnace body and fixed parallel to the winding shaft in the upper winding chamber. The winding and unwinding system is adjusted so that it does not deflect during operation.
[0086] Specific methods are as follows Figure 13As shown. In this embodiment, within the allowable range of winding and unwinding lengths, three bundles of uniformly high-quality montmorillonite copper wire can be directly obtained.
[0087] Example 4: Roll-to-roll single crystallization and surface graphene growth of 50 μm diameter copper wire
[0088] The process is the same as in Example 1, using a 50 μm diameter copper wire, and in step 1), the winding tension is set to 0.02 N. In this example, a 50 μm diameter montmorillonite single-crystal copper wire is obtained.
[0089] Comparative Example 3: Horizontal CVD growth of copper wire in a horizontal roll-to-roll system
[0090] 1) Secure the neatly bundled commercial copper wire material to the... Figure 14 The copper wire is placed on the unwinding shaft of the unwinding chamber of the horizontal roll-to-roll chemical vapor deposition (CVD) growth apparatus shown. The beginning end of the copper wire is then passed through the tubular furnace body and fixed to the winding shaft of the winding chamber, with the winding tension set to 0.3 N. The CVD high-temperature reaction chamber is then evacuated to low pressure.
[0091] 2) Under an inert atmosphere (argon, partial pressure 90 kPa), the CVD reaction chamber is heated from room temperature to the target temperature within 1 h. The temperatures of the five temperature zones from left to right are set to 980℃, 990℃, 1000℃, 1010℃ and 1020℃, respectively, and the length of each temperature zone is about 10 cm.
[0092] 3) Maintain the chamber temperature and switch the gas to a mixture of argon, hydrogen and acetylene (argon is used as a supplementary gas to balance the pressure), argon 90 kPa, hydrogen 1 kPa, acetylene 0.1 Pa.
[0093] 4) Start the unwinding and rewinding mechanisms, and set both the unwinding and rewinding speeds to 100 mm / min.
[0094] 5) Maintain the conditions described in 3) until the copper wire bundle is completely wound to the take-up end.
[0095] Except for the roll-to-roll system structure itself, this comparative example maintains the same implementation conditions as Example 1. However, due to the frictional resistance between the copper wire and the substrate during horizontal transmission (affected by the substrate material and surface structure), the actual tension is not stable. Figure 15 As shown, the wound copper wire exhibited some bending and premature breakage, failing to achieve the complete preparation of the intended length of montmorillonite copper wire. Furthermore, as... Figure 16 As shown, the side of the copper wire that contacts the substrate also caused some dirt and graphene damage.
[0096] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be practiced in a wide range of ways with equivalent parameters, concentrations, and conditions without departing from its spirit and scope, and without requiring unnecessary experiments. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including changes made using conventional techniques known in the art that depart from the scope disclosed herein.
Claims
1. A continuous preparation method for montmorillonite single-crystal copper wire material, comprising the following steps: Using vertical roll-to-roll technology, copper wire is fastened to the unwinding shaft in the lower unwinding chamber, with its starting end passing through the tubular furnace body from bottom to top and fixed to the winding shaft in the upper winding chamber. A specific tension is applied at the winding end, and a specific temperature gradient is applied along the copper wire's running direction at a certain winding speed to promote the continuous growth of copper single crystal grains. At the same time, carbon source gas is introduced into the chamber, and graphene is grown by chemical vapor deposition (CVD). After continuous growth, graphene single crystal copper wire material is obtained. Among them, when the CVD growth temperature is ≥940℃ and the copper wire diameter is 200~400 μm, the tension applied at the winding end is... F Satisfying 8 mN≤ F ≤0.3 N; CVD growth temperature ≥ 940℃, copper wire diameter 50~100 μm, tension F applied at the winding end satisfies 0.5 mN ≤ F ≤0.02 N; The winding speed R Satisfying 10 mm / min≤ R ≤100 mm / min; Along the direction of the copper wire, the temperature gradient increases, and the temperature gradient is 0.5~4℃ / cm, with the highest temperature being 980~1040℃.
2. The method according to claim 1, characterized in that, The method is implemented using a vertical roll-to-roll CVD equipment, wherein the winding and unwinding mechanism of the vertical roll-to-roll CVD equipment is equipped with a precision tension control unit.
3. The method according to claim 1, characterized in that, The total pressure of the chamber is not less than 2000 Pa; the carbon source gas is methane or acetylene.
4. The method according to claim 1, characterized in that, Preparation of monolayer graphene-coated montmorillonite single-crystal copper wire with controlled Pa ≤ 1 P CH4 ≤5 Pa, or 0.05 Pa≤ P C2H2 ≤0.2 Pa, 100 Pa≤ P H2 ≤1000 Pa, P CH4 、P C2H2 、P H2 These are the partial pressures of methane, acetylene, and hydrogen, respectively. Preparation of multilayer graphene-coated montmorillonite single-crystal copper wire with Pa controlled at 10 ≤ P CH4 ≤50 Pa, or 0.2 Pa≤ P C2H2 ≤1Pa, 2000 Pa≤ P H2 ≤20000 Pa, P CH4 、P C2H2 、P H2 These are the partial pressures of methane, acetylene, and hydrogen, respectively.
5. The method according to claim 1, characterized in that, Multiple bundles of independently wound copper wires with a certain interval are placed at the unwinding end to achieve coaxial parallel growth of multiple bundles.
6. A continuous preparation method for single-crystal copper wire material, comprising the following steps: Using vertical roll-to-roll technology, the copper wire is fastened to the unwinding shaft in the lower unwinding chamber, so that its starting end passes through the tubular furnace body from bottom to top and is fixed to the winding shaft in the upper winding chamber. A specific range of tension is applied at the winding end, and a specific temperature gradient is applied along the copper wire running direction at a certain winding speed to promote the continuous growth of copper wire grains. Among them, when the temperature is ≥940℃ and the copper wire diameter is 200~400 μm, the tension applied at the winding end is... F Satisfying 8 mN≤ F ≤0.3N; Temperature ≥ 940℃, copper wire diameter 50~100 μm, tension F applied at the winding end satisfies 0.5 mN ≤ F ≤0.02 N; The winding speed R Satisfying 10 mm / min≤ R ≤100 mm / min; Along the direction of the copper wire, the temperature gradient increases, and the temperature gradient is 0.5~4℃ / cm, with the highest temperature being 980~1040℃.
Citation Information
Patent Citations
Preparation method of monocrystalline metal nanowire array based on alumina template
CN102732963A
Graphene metal composite wire and low-temperature continuous preparation method thereof
CN111058017A